MANAGEMENT OF ORGANIZING FROM THE PERSPECTIVE OF THE QUR'AN AND HADITH IN THE MODERN ERA - Nuryanti; Fauji, Imam (Journal of Social Science, 2025)
Objective: This study aims to analyze the principles of organizing management from the perspective of the Qur'an and hadith and its relevance in the modern era. The research explores how Islamic teachings provide a framework for effective organizational management that aligns with contemporary demands. Method: Using a qualitative approach, the study employs a literature review method, collecting and analyzing data from 15 relevant articles. The data are processed through problem formulation, comparative analysis, and synthesis to draw conclusions. Results: The findings reveal that the concepts of organizing management outlined in the Qur'an and hadith emphasize values such as trust (amanah), consultation (shura), justice (‘adl), and accountability (muhasabah). These principles demonstrate high relevance when applied to modern organizational systems, providing a robust foundation for fostering collaboration, efficiency, and ethical practices in organizational development. Novelty: This study contributes to the existing body of knowledge by bridging classical Islamic principles with modern management practices, highlighting the applicability and timelessness of Qur'anic and prophetic teachings in addressing contemporary organizational challenges.